Perspectival Ontology: Between Situated Knowledge and Multiculturalism. (9th March 2022) - Massimi, Michela
Abstract: In this paper I give an overview of a perspectival realist ontology. I discuss the role of situated knowledge and multiculturalism in perspectival ontology and offer a working definition of 'phenomena' as the minimal unit of such ontological commitment. I clarify how the view (and underlying notion of scientific perspective) differs from Kuhn's view, and highlight some of its implications for how to think of scientific knowledge as a multicultural and cosmopolitan inquiry.